PENGARUH PBRILAKU SUPERVISI AKADEMIK PENGAWAS SEKOLAH TERHADAP KINERIA GURU DI UPT DISDIKPORA KECAMATAN GANDRUNGMANGU KABUPATEN CILACAP - , Sugiman ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study is aimed to measure the effect of the behavior of academic supervision by the school superintendent on the performance of elementary school teachers in UPT Disdikpora Gandrungmangu Cilacap Regency. The data were obtained by distributing questionnaires about school superintendent supervision behavioral effects on performance of elementary school teachers in UPT Disdikpora Gandrungmangu District District Cilacap Regency